Determinants Influencing Study Program Selection Controlled by Program Image: A Survey of Students at FITK UIN Sunan Kalijaga from 2019 to 2022 - Nispi Ani Barus (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to find out and analyze the relationship and magnitude of the influence of determinant factors on the selection of controlled study programs through the image of the study program. The theories used are the theory of consumer behavior by Hawkins regarding factors that affect decisions and the theory of image by M. Mayne Delozier. The research was conducted at the Faculty of Tarbiyah and Teacher Training UIN Sunan Kalijaga with a population of 2,612 FITK students. Technique sampling using probability sampling using the cluster method sampling so that 336 student respondents were obtained. In this study, the dependent variable is in the form of student decisions and the independent variable is in the form of infrastructure, location, UKT, promotion, parental role, culture, and Extracurricular. As well as the control variable in the form of the image of the study program. Data collection using questionnaires and documentation. The collected data is processed and analyzed using descriptive statistical analysis and inferential statisticsusing SPSS (Statistical Package for Social Sciences) version 25.